A Comparison of Cohomological Obstructions to the Hasse Principle and to Weak Approximation - Tian, Yisheng (Comptes Rendus. Mathématique)
We show that certain Tate–Shafarevich groups are unramified which enables us to give an obstruction to the Hasse principle for torsors under tori over $p$-adic function fields.